ACTIVATING STUDENTS’ INTEREST THROUGH WONDERSHARE QUIZ CREATOR SOFTWARE IN READING COMPREHENSION - Ismail Sangkala; Baso Jabu; Andi Muliati (ELT Worldwide: Journal of English Language Teaching, 2019)
This research aimed at finding out whether or not the use of “Wondershare QuizCreator Software” activates the students’ interest in reading comprehension of theEnglish Education Program, Faculty of Teacher Training and Education,Muhammadiyah University of Makassar, Indonesia. In academic Year 2012/2013,based on investigating students’ interest in learning of reading comprehensionthrough Wondershare Quiz Creator Software. The research employed the trueexperimental method. This research assigned two groups namely experimentalgroup and control group. Each group consisted of 45 students. The sample waschosen by applying cluster random sampling technique. The researcher used thequestionnaire was given to the students to cover the statements about the students’ interest in the implementation of software in reading comprehension. The data obtained through Likert Scale, it was analyzed by using descriptive and inferential statistics through SPSS 16.0 version. In conducting the research, the researcher applied the “Wondershare Quiz Creator Software” and the result showed that there was students’ interest at the experimental group after applying the software. It was proven by the result of descriptive and inferential statistics in questioning the students’ statements in the posttest. Based on the result of the questionnaire engaged to the experimental group, the interest of the students was dominantly classified as very high interest. There were 12 (27%) of them classified as high interest and 33 students dominated 73 % as very high interest. The students in the experimental group generally agree with the implementation of the software because they had confidence and felt more enthusiastic with the mean score is 86.53, which was categorized as interesting.